Prevention of the social isolation of older persons: the impact of community environmental satisfaction on social isolation - Sen Ma; Gang Lou; Yifan Duan (Frontiers Media S.A., 2023)
BackgroundTo explore how to prevent the social isolation of the older adult, this study constructed a model of the influence of community environmental satisfaction on the social isolation of the older adult from the three dimensions of environmental facilities, transportation, and supporting facilities around the community. Methods: The social network scale and environmental satisfaction scale were used to collect the sample data of nine communities in Xi'an, and the maximum likelihood estimation method was used to analyze the data and test the model.Results(1) Environmental facilities, transportation, and community surrounding facilities promoted community environment satisfaction (R2 = 0.904). Among them, environmental facilities (β = 0.869) had the greatest impact on community environmental satisfaction, followed by transportation (β = 0.118), and surrounding facilities (β = 0.084) had the least impact on community environmental satisfaction. (2) Environmental satisfaction had a direct positive impact on social isolation. Among them, the impact of environmental satisfaction on friend isolation (R2 = 0.895, β = 0.829) was greater than that on family isolation (R2 = 0.718, β = 0.747).ConclusionEnvironmental satisfaction can directly affect the social isolation of the older adult in the community and can be used as an intermediate variable of environmental facilities, transportation, and surrounding facilities in the community so that it can indirectly affect the social isolation of the older adult. The results of this study provide a scientific basis for the design of aging environments in the future.